Sprache - Kognition - Kultur. Sprache zwischen mentaler Struktur und kultureller Prägung - Eichinger, Ludwig (Jahrbuch des Instituts für Deutsche Sprache, 2008)
This Yearbook of the German Language Institute aims to call to mind the traditions of linguistics in cultural studies and at the same time to document the connections between linguistics and modern research paths in cultural studies such as the theory of cognition and discourse analysis. In addition, the papers illuminate the linguistic turn in literary and historical studies. Thus the volume presents the foundations and theoretical and methodological approaches to linguistics as a cultural study, together with examples related to practice.